Developing Teachers' Skills in Designing Project-Based Learning in the Merdeka Curriculum through Assembler Edu Training - Siswanto, Deny Hadi; Putri, Helena Anggraeni; Susanto, Doni (Civitas : Jurnal Pengabdian Masyarakat, 2024)
This study aims to identify and describe: (1) the level of teacher satisfaction with the introduction of project-based learning in the Merdeka Curriculum through Assembler Edu training; (2) the relevance of Assembler Edu training for project-based learning in the Merdeka Curriculum in relation to the teachers' primary responsibilities; (3) teachers' feedback on Assembler Edu training for designing project-based learning within the Merdeka Curriculum. The study is quantitative and employs descriptive analysis. The training was conducted to assist teachers in designing projects using Assembler Edu. Data analysis reveals a highly positive response from teachers towards the training. Teachers reported satisfaction with the Assembler Edu training and found it valuable for understanding their role as facilitators of the Pancasila Student Profile. Additionally, the training is relevant to teachers' needs and encourages them to implement project-based learning in alignment with the Merdeka Curriculum by utilizing Assembler Edu.